Identification and Antibiotic Profiling of Wohlfahrtiimonas chitiniclastica, an Underestimated Human Pathogen - Kopf, Anna; Bunk, Boyke; Coldewey, Sina M.; Gunzer, Florian; Riedel, Thomas; Schröttner, Percy (Frontiers in Microbiology, 2021)
In the past 12 years, several case reports have shown that Wohlfahrtiimonas chitiniclastica is capable of causing sepsis and bacteremia in humans. However, since most clinicians are not familiar with this species, little is known about its pathogenicity and treatment options while it has recently been described as rare but underestimated human pathogen. Therefore, a larger strain collection is required so that methods can be identified that are most suitable to obtain rapid and reliable identification. Moreover, the antimicrobial resistance profile needs to be elucidated in order to explore possible treatment options.